COVID-19 Private Pension Withdrawals and Unemployment Tenures - Tristram Sainsbury; Robert Breunig; Timothy Watson (Institute of Labor Economics (IZA), 2022)
This is the first study to evaluate the effects of early pension withdrawal policies on tenures on unemployment payments in the COVID-19 context. We use a novel set of linked whole-of-population administrative records to examine more than half-a-million Australians who found themselves newly on an unemployment payment in the initial months of the COVID-19 pandemic. We estimate that receiving a lump sum of up to A10,000 from superannuation accounts at the most acute phase of the pandemic, between April and June 2020, resulted in a 32 per cent lower exit rate from unemployment benefits inside the first six months of a spell on benefits, and 14 per cent inside a year of spell. Receiving a lump sum during the second window of opportunity – mostly in July and August 2020 and as a labour market recovery was underway – resulted in a 34 per cent lower exit from unemployment benefits inside the first nine months of spell, and 14 per cent inside fifteen months of spell. The jobseeking deterrence is ultimately temporary but it took close to eighteen months for an estimated convergence between withdrawers and those that didn't withdraw. 162,000 withdrawers with completed spells on average spent an additional 7 weeks on unemployment payments, translating to 8 million additional days in aggregate, and implying A580 million in additional pandemic fiscal expenditure.
Keywords: E24; H12; H30; H53; J32; 330; unemployment; crisis management; fiscal policy; government expenditure; unemployment benefits; welfare programs; private pensions